2013
DOI: 10.2355/isijinternational.53.698
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Gas Metal Arc Welding Process Using an Analytically Determined Volumetric Heat Source

Abstract: High peak temperature and continuous deposition of electrode droplets in the weld puddle inhibit realtime monitoring of thermal cycles and bead dimensions in gas metal arc welding. A three-dimensional numerical heat transfer model is presented here to compute temperature field and bead dimensions considering a volumetric heat source to account for the transfer of arc energy into the weld pool. The heat source dimensions are analytically estimated as function of welding conditions and original joint geometry. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Similar studies to analytically estimate the bead profile are reported earlier for butt joint configuration. 37, 38 In contrast, the filler wire deposit profile in lap joint of aluminium to steel will be governed by the melting of aluminium sheet and filler wire, and the spread of molten filler over the unmelted steel surface. Figure 2 shows a presumed cross-section of the filler wire deposit profile encompassed by four line segments , , and , and the circular arc BED.…”
Section: Theoretical Formulationmentioning
confidence: 99%
“…Similar studies to analytically estimate the bead profile are reported earlier for butt joint configuration. 37, 38 In contrast, the filler wire deposit profile in lap joint of aluminium to steel will be governed by the melting of aluminium sheet and filler wire, and the spread of molten filler over the unmelted steel surface. Figure 2 shows a presumed cross-section of the filler wire deposit profile encompassed by four line segments , , and , and the circular arc BED.…”
Section: Theoretical Formulationmentioning
confidence: 99%
“…Several studies estimating the bead profiles for butt and lap joint configuration indicate the bead dimension in lap joint is decided by deposition of molten filler wire and aluminum base metal, and the spread of molten filler to the steel surface. [13,14] The dimension of wire deposited bead profile is presumed as Fig. 2.…”
Section: Introductionmentioning
confidence: 99%